Психолінгвістична діагностика - Засєкіна, Лариса Володимирівна; Zasiekina, Larysa Volodymyrivna; Засєкін, Сергій Васильович; Zasiekin, Serhii Vasyliovych (Волинський національний університет імені Лесі Українки, 2008)
Книга висвітлює ключові психолінгвістичні підходи до аналізу усного й писемного мовлення. Автори визначають об'єкт, предмет, мету та завдання психолінгвістики як самостійної галузі знань, її сучасний стан і перспективи; окреслюють провідні методи аналізу політичних, рекламних, художніх текстів. Подана психолінгвістична експертиза ксенофобії на матеріалі текстів друкованих ЗМІ; аспекти мовленнєвої генези дітей дошкільного віку. The book is focused on the main psycholinguistic methods of oral and written discourse analysis. The authors define the object, goal and objectives of psycholinguistics as an independent field of knowledge, its today's state and prospects. Moreover, the main tools of political, advertising, literary texts along with psycholinguistic expert analysis of the regional press have been discussed. Finally, some aspects of pre-school children's language genesis have been highlighted.
For psycholinguists, linguists, psychologists, Ph.D. students, students of higher educational institutions who study Psycholinguistics, Linguistic Expert Analysis, Introduction to Structural Linguistics.
Keywords: психолінгвістика; Psycholinguistics; психолінгвістична експертиза; psycholinguistic expert analysis; контент-аналіз; content analysis; інтент-аналіз; intent analysis; усне/писемне мовлення; oral/written discourse